Alban Berg: Master of the smallest link - Adorno, Theodor W. 1903-1969; Brand, Juliane; Hailey, Christopher (Cambridge Cambridge University Press, 1991)
Adorno's study of Austrian composer Alban Berg (1885-1935) is a sui generis document. In addition to Adorno's personal account of of the life and musical works of his mentor, friend, and composition teacher, the book explores the historical and cultural significance of Berg's music, its relationship to that of other nineteenth- and twentieth-century composers, and to the larger issues of contemporary life.
For the original text in German, see PHI ADOR a
Originally published in 1965
Keywords: Berg, Alban -- 1885-1935; 20th Century (1901-2000); Composer; Biography; Musical analysis; Vienna (Austria)